Enantioselective Synthesis of Cryptopleurine and Boehmeriasin A via Organocatalytic Intramolecular Aza-Michael Addition - Zeng, Chuanqi; Liu, Hanbin; Zhang, Mengyao; Guo, Jiajia; Jiang, Shunchao; Yu, Shouyun (Synlett, 2012)
The enantioselective synthesis of phenanthroquinolizidine alkaloids cryptopleurine and boehmeriasin A was achieved in eight steps from commercial available Cbz-protected 2-piperidinone in 22% and 20% overall yield, respectively. The key steps of this route are intramolecular enantioselective aza-Michael addition, intramolecular aldol addition, and oxidative coupling.
Keywords: alkaloids; enantioselectivity; ketones; Michael addition; total synthesis